Polyhalite as an alternate nutrient source for improving growth, yield, and nutrient use efficiency in onion and garlic - Thangasamy Arunachalam; Komal Gade; Payal Arun Mahadule; Abhishek Khalate; Neeraj K. Awasti; Vipin Mishra; Vijay B. Mahajan (Scientific Reports)
Abstract Polyhalite (POLY4), a naturally occurring multi-nutrient source with a low salt index, has potential as a replacement for muriate of potash (MOP). A field experiment was conducted to assess the effect of POLY4 on the growth, yield, quality, and nutrient use efficiency of onion and garlic, comparing nine fertilizer treatments. The results indicated that applying 100% POLY4 alone significantly enhanced the yield and nutrient uptake of both crops compared to plots treated with 100% K and S from MOP and bentonite S. Notably, potassium uptake in the POLY4 treatment exceeded the amount of potassium applied through fertilization, indicating that the crops may have mobilized additional potassium from soil reserves, which could raise concerns regarding the long-term sustainability of soil nutrient levels. However, the combination of 100% POLY4 with additional K resulted in a 6.3% yield increase in 2022–2023 and a 4.0% increase in 2023–2024 compared to the MOP treatment. This combined treatment produced statistically similar results to the MOP treatment for garlic in both years. Additionally, it significantly enhanced pyruvic acid and total protein concentrations in both crops and resulted in higher total dry matter yield and N, P, K, and S uptake. Moreover, agronomic efficiency, partial factor productivity, and recovery efficiency were notably higher in plots receiving 100% POLY4 with K. Due to its lower cost and reduced chloride content, 100% recommended S through POLY4, supplemented with K from MOP, could be recommended for sustainable onion and garlic production and improved soil health.